2017
DOI: 10.1002/alr.22012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating real‐time effects of topical 1:1000 epinephrine in endoscopic sinus and skull‐base surgery on hemodynamic parameters through intraoperative arterial line monitoring

Abstract: Although intranasal topical 1:1000 epinephrine use showed no substantial hemodynamic changes in the majority of patients, in a subset of patients it can cause significant transient elevations in blood pressure to a degree necessitating intervention. Topical epinephrine should be used judiciously in endoscopic sinus surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 11 publications
5
34
1
Order By: Relevance
“…Two of 28 patients in this study had an SBP increase of >75 mmHg after pledget placement. There were no confounding factors identified in these patients, similar to our previous study . We observed a lower percentage of responders in this study compared with our previous study .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Two of 28 patients in this study had an SBP increase of >75 mmHg after pledget placement. There were no confounding factors identified in these patients, similar to our previous study . We observed a lower percentage of responders in this study compared with our previous study .…”
Section: Discussionsupporting
confidence: 89%
“…Orlandi et al observed 2 patients who had cardiovascular complications after topical epinephrine placement . Our group previously found that 6 of 26 patients had severe spikes in SBP after topical treatment . Our current results provide further supporting evidence that topical epinephrine may induce significant hemodynamic changes in a subset of sensitive individuals.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Evidence‐based evaluation of the safety profile of concentrated topical epinephrine is based on a systematic review of clinical trials (level 1 evidence), two prospective cohort studies (level 2 evidence), and two retrospective studies (level 3 evidence) …”
Section: Level Of Evidencementioning
confidence: 99%